(untitled) (Annals of Bangladesh Agriculture, 2022)
This study aimed to evaluate the soil chemical properties of a jackfruit-based multistoried agroforestry system of a farmer’s field in Belabo upazila of Narsingdi district located in the central terrace ecosystem of Bangladesh. The three-storied of crops viz. upperstorey - jackfruit trees; middlestorey - papaya, lemon, mandarin and sweet orange and lowerstorey - seasonal vegetables such as eggplant, bottle gourd and ash gourd were included in the system. The experiment was conducted in a randomized complete block design with three replications. There were five treatments covering agroforestry with four orientations and sole cropping (jackfruit trees). The agroforestry system improved the chemical properties of top soil layer compared to the sole cropping with jackfruit trees. Soil pH (4.62), total nitrogen (0.081%), organic carbon (0.61%), organic matter (1.05%), phosphorus (4.23 ppm), sulphur (10.17 ppm), calcium (2.27 meq/100g), magnesium (0.46 meq/100g) and potassium (0.52 meq/100g) were recorded in the agroforestry systems that were higher than those of the soil properties of sole cropping (jackfruit trees). The result revealed that practicing agroforestry can help in improving the soil fertility status for successful sustainable crop production. Ann. Bangladesh Agric. (2021) 25 (1) : 105-115